Identification of phenolic compounds in crude methanolic extract of Piper sarmentosum leaves - Mustafa, Farah Farisha; Ibrahim, Maizatul Akma; Mohamad, Habsah (2017)
Herbal plants are rich sources of secondary metabolites such as phenolics which can be beneficial to improve human health. Previous studies reported that phenolic compounds could lower the risk of heart diseases, occurrence of cancers as well as microbial infections. Piper sarmentosum or locally known as Kaduk is a tropical herb plant that is well established for many traditional medicinal purposes. These benefits may depend significantly on the phenolic content. Hence, the identification of phenolic compounds in this plant is necessary. The objective of the present study was to identify the phenolic compounds in crude methanolic extract of Piper sarmentosum leaves. Total phenolic content was determined spectrometrically according to Folin-Ciocalteu procedures. The characterization of the phenolic compounds was examined using reverse phase HPLC and GC-MS analyses. The total phenolic content was found to be 142.72 mg[GAE]/g of the Kaduk leaves extract. The presences of gallic acid, tannic acid, quercetin and naringenin were identified from the RP-HPLC analysis. From GC-MS analysis, the presences of elemicine, myristicine, methyleugenol and hydrocinnamic acid were revealed. Our findings provided the evidence that crude methanolic extract of Piper sarmentosum leaves contains high content of active phenolic compounds that might have the potential to be incorporated as the basis ingredient in medicines to treat various diseases in Malaysia.